AB0335 Are eular rheumatoid arthritis (RA) management recommendations applicable at the country level? similarities and differences with the recent french ra management recommendations. (12th June 2018) - Hua, C.; Daien, C.; Gaujoux-Viala, C.; Cantagrel, A.; Dubremetz, M.; Dougados, M.; Fautrel, B.; Mariette, X.; Nayral, N.; Richez, C.; Saraux, A.; Thibaud, G.; et al.
Abstract : Background: Recently, EULAR updated the rheumatoid arthritis (RA) management recommendations. 1 2 In 2018, the French Society of Rheumatology (SFR) updated their recommendations regarding the management of RA. 3 This gave us the opportunity to compare the recommendations. Objectives: To update the 2014 French recommendations for the management of RA and to compare them to the EULAR recommendations. Methods: The SFR approach was based on the literature and on expert opinion. A systematic literature review (SLR) was performed by 2 fellows, collecting data to answer 11 questions. The previous (2014) recommendations were updated by a committee including 11 rheumatologists, 2 patients and 1 healthcare professional, during a 1 day meeting in January 2018. The recommendations were compared to the recently issued EULAR recommendations. 1 2 Results: The SLR included 137 papers. The consensus process led to 4 overarching principles and 15 recommendations. The overarching principles emphasise the need for shared decisions between the rheumatologists and the patient and the importance of a global approach of RA including pharmaceutical and non-pharmacological management. The recommendations address the diagnostic phase of RA, early initiation of disease-modifying antirheumatic drugs (DMARDs) and the usefulness of regular disease activity assessments through validated composite indices with a target of clinical remission or low disease activity. As first strategy, the expert committee recommends methotrexate (MTX). In case of intolerance or inadequate response to MTX, treatment must be optimised. If unfavourable prognostic markers are present, adding a targeted treatment (either biologic or synthetic) can be proposed, at best in combination with MTX; if not, switching to another conventional synthetic DMARD (csDMARD) or combined csDMARDs therapy can be proposed. While waiting for csDMARDs efficacy, short term (less than 6 months) glucocorticoids (GC) can be proposed. Second-line and further treatments and management of remission are also addressed, as well as the importance of managing comorbidities and of non-pharmacological measures. Conclusions: These recommendations are designed to improve the management of RA and are concordant with the recent EULAR recommendations on several items. Main differences concern the place of GC and of combined csDMARD therapy, as well as additional points on diagnosis, non-pharmacological measures, comorbidities and the importance of a global approach. References: [1] Smolen JS, Landewé R, Bijlsma J, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2016 update. Ann Rheum Dis2017;76(6):960–77. [2] Combe B, Landewe R, Daien CI, et al. 2016update of the EULAR recommendations for the management of early arthritis. Ann Rheum Dis2017;76(6):948–59. [3] Gaujoux-Viala C, Gossec L, Cantagrel A, et al. Recommendations of the French Society for Rheumatology for managing rheumatoid arthritis. Jt Bone Spine Rev Rhum2014;81(4):287–97. Disclosure of Interest: None declared